Pemeriksaan Diagnostik COVID-19 : Studi Literatur - Halbina Famung Halmar; Nur Febrianti; Maria Kurnyata Rante Kada (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: The purpose of this literature study is to find out which diagnostic tests are used to detect COVID-19. Method: Articles collected from 2020 using 3 databases (Pubmed, Science Direct and Google Scholar) obtained 14 articles that fit the inclusion criteria. Results: CT-Chest examination has a high sensitivity for diagnosis of COVID-19 compared to Real-Time Polymerase Chain Reaction (RT-PCR) in the initial phase. The IgG and IgM combination test has better utility and sensitivity compared to the IgG or IgM test alone. Conclusion: Examinations carried out to detect COVID-19 accurately and precisely must combine RT-PCR, CT-Chest and Rapid Test.